Sirolimus induces depletion of intracellular calcium stores and mitochondrial dysfunction in pancreatic beta cells - Lombardi, Angela (Sci Rep, 2017)
Sirolimus (rapamycin) is an immunosuppressive drug used in transplantation. One of its major side effects is the increased risk of diabetes mellitus; however, the exact mechanisms underlying such association have not been elucidated. Here we show that sirolimus impairs glucose-stimulated insulin secretion both in human and murine pancreatic islets and in clonal β cells in a dose- and time-dependent manner. Importantly, we demonstrate that sirolimus markedly depletes calcium (Ca(2+)) content in the endoplasmic reticulum and significantly decreases glucose-stimulated mitochondrial Ca(2+) uptake. Crucially, the reduced mitochondrial Ca(2+) uptake is mirrored by a significant impairment in mitochondrial respiration. Taken together, our findings indicate that sirolimus causes depletion of intracellular Ca(2+) stores and alters mitochondrial fitness, eventually leading to decreased insulin release. Our results provide a novel molecular mechanism underlying the increased incidence of diabetes mellitus in patients treated with this drug.